Fiber and Chemical Characteristics of Branchwoods of Three Meranti Species - Danang S Adi; Lucky Risanto; Ika Wahyuni; Sukma S Kusumah; Wahyu Dwianto; Taka Hayashi (Jurnal Ilmu dan Teknologi Kayu Tropis, 2011)
The fiber and chemical characteristics of branchwoods of three meranti species namely meranti sangkan, meranti bakau, and meranti bunga kulit hitam from Bukit Batu Peat Swamp Forest, Riau were observed. The aim of this research was to discover the potential utilization of these three meranti species based on their characteristic. The result showed that holocellulose contents of meranti sangkan, meranti bakau, and meranti bunga kulit hitam were 72.97%, 75.28%, and 69.88%, whereas the α-cellulose contents were 43.55%, 51.14%, and 43.25%, respectively. meranti sangkan had the highest lignin content (35.99%) followed by meranti bakau (34.21%) and meranti bunga kulit hitam (32.18%). meranti Bunga kulit Hitam had the highest extractive content (2.24%) followed by meranti sangkan (1.66%) and meranti bakau (1.08). Furthermore, the fiber length of meranti bunga kulit hitam, meranti sangkan, and meranti and meranti Hitam were 1475.45 μm, 1475.45 μm, 1442.62 μm, and 1205.23 μm, respectively. The values of fiber derivative of the three meranti species were slightly differ from class I, except for felting power that was classified in class III. The result also showed that the branchwoods of the three meranti species are suitable for pulp and paper raw material.Key words: fiber and chemical properties, meranti bakau, meranti sangkan, meranti bunga kulit hitam, peat swamp forest